Біоморфологічні та демографічно-популяційні особливості смілки ситника (Silene sytnikii Krytzka, Novosad et Protopopova) в Кодимо-Єланецькому Побужжі - Shcherbakova, O.F.; Novosad, V.V.; Krytzka, L.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
Indication of life forms, peculiarities of ontomorphogenetic, matters of populations demography and protection of the rare, endemic and relict species Cоdymo-Elanetsky Bug region – Silene sytnikii Krytzka, Novosad et Protopopova was consideration.